(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
When it comes to making smart investments, financial literacy is a mix of awareness,knowledge, skill, attitude, as well as conduct. In other words, financial literacy is the acquaintance with themost fundamental economic principles essential for making reasonable saving and investing choices.For this work, we are interested in finding out how well service and business class persons understandfinancial concepts. It has been shown that persons in the service and business classes have an averagedegree of financial knowledge based on a semi-structured questionnaire.The financial literacy of SLIIT’sbusiness students is examined in this research. The study’s goal was to find out how well businessstudents are prepared financially and whether or not the educational system is doing its part to assistthem do so. Fifty completed questionnaires were approved for analysis after they were used to gatherdata. Using the mean marks of correct responses from the sample, the survey participants were dividedinto two sub-groups. Undergraduates typically get a GPA of 3.60. Categorical characteristics such asgender, advanced level stream, specialist areas, as well as other accounting and finance-relatedprofessional and academic skills, may be used to assess a person’s financial literacy level. Businessmanagement students have a poor to medium degree of financial literacy based on the findings of thisstudy. It is imperative that the institution provide additional courses and seminars on financial concernsto assist students better manage their own financial problems.